Improving Creative Thinking Skills through Integration of Problem-Based Learning with STEAM In Environmental Pollution Material - Ade Suryanda; Mieke Miarsyah; Aby Hanhan Ulil Abshor Kosasih (Jurnal Penelitian Pendidikan IPA, 2023)
The 21st century demands today's students to face increasingly complex life problems and a globally rigorous work environment. A learning model that can facilitate learners in developing their creative thinking skills is necessary. The objective of this research is to determine the influence of PBL-STEAM integration on learners' creative thinking abilities in the topic of environmental pollution. This type of research is quantitative with quasi-experimental research methods. The research sample consisted of 58 learners, with each class consisting of 29 learners selected through simple random sampling. Based on hypothesis testing using independent t-test at Î± = 0.05, the research findings showed a significance value of 0.00, this suggests that the PBL-STEAM learning model has an effect on learners' creative thinking in the topic of environmental pollution. The influence of the PBL-STEAM model on learners' creative thinking abilities can be analyzed based on the syntax of learning within the PBL-STEAM model. The results of this research imply that the PBL-STEAM learning model can be employed as a substitute for a model that enhances students' creative thinking abilities in the topic of environmental pollution